Penerapan Maqomah sebagai Pengembangan Materi Pembelajaran Al-Quran Hadits di Madrasah Aliyyah Al-Falah Nagreg - Saputra, Wahyu Andi; Nugraha, Mulyawan Safwandy (ALSYS, 2024)
This research aims to analyze implementation of Maqomah as a development of Quran and Hadith learning materials at Madrasah Aliyyah Al-Falah Nagreg. The research method used is a descriptive qualitative approach. The study will be conducted at Madrasah Aliyyah Al-Falah Nagreg and will involve an initial literature review to understand the theories and concepts underpinning the research. Subsequently, the research will go through several phases, including preparation, data collection through classroom observations, interviews with teachers and students, and analysis of documents and teaching materials. The data obtained will be analyzed using qualitative text analysis techniques. This research aims to provide a deeper understanding of the application of Maqomah in Quran and Hadith learning at Madrasah Aliyyah Al-Falah Nagreg and its impact on student understanding. The research findings are expected to provide valuable insights into the use of this method in the context of Islamic education in madrasah. Thus, this research can make a significant contribution to improving the quality of religious education in an Islamic educational environment.